Testing surface irrigation method for cash crops to apply in Mekong delta - Vietnam - Nguyễn, Văn Liêm (Wageningen Agricultural Univ, 1991)
In this study, the main objective is to compare the economic and technical performance of furrow and basin irrigation with the traditional bucket irrigation method. The additional objective in support of the main objective is the determination of phisical soil characteristics, in particular the capillary rise of water from the groundwater into the rootzone and the infiltration characteristics of the soil